FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN PEMERIKSAAN SADARI PADA WUS - Wulandari, Yeni; Rohaya, Rohaya; Pastuty, Rosyati; Suprida, Suprida; Septeria, Indah Puji (stikes 'aisyiyah palembang, 2026)
Background: Cancer control is prioritized on prevention and early detection of breast cancer using the Clinical Breast Examination (SADANIS) method and the Self-Breast Examination (SADARI) method. Research Objective: To determine the factors associated with SADARI examinations among reproductive-age women (WUS) in Pangkalan Jaya Village, Babat Toman District. Method: This research is a descriptive analytical study with a cross-sectional approach, using the chi-square test, and the sampling technique used was probability sampling with a simple random sampling method. The sample size was 73 people, and univariate and bivariate analyses were used in this study. This research was conducted on March 24-May 28, 2025, in Pangkalan Jaya Village, Babat Toman District, Musi Banyuasin Regency. Results: Statistical test results with chi-square obtained the results there is a significant relationship between age p-value <0.001 (p<0.05), education p-value 0.002 (p<0.05), family history of breast cancer p-value <0.001 (p<0.05) with knowledge of SADARI examination. Suggestion: increase health promotion, community-based counseling, and involve health cadres and community leaders in disseminating information about BSE so that health messages are better received by the community. Keywords : Education, Breast Cancer History, SADARI, Age, WUS